On reliability approach for testing of many distributions for pair of Markov chains - Evgueni Haroutunian; Naira Grigoryan (Изд-во НАН РА)
The problem of three hypotheses logarithmical asymptotically optimal testing for a pair of simple homogeneous stationary Markov chains is examined. It is supposed that M probability distributions are known and each of Markov chains independently of other follows to one of them. The matrix of all error probability exponents (reliabilities) is studied.
Keywords: Mathematics